PENERAPAN MODEL PEMBELAJARAN THINK, WRITE, AND TALK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN KEWIRAUSAHAAN - Henny Zurika Lubis (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to improve students' activity and learning outcomes through theapplication of thinking, write, and talk learning models as an effort to improve thequality of learning in entrepreneurship courses. The research method used isclassroom action research procedure, with data collection techniques in this studyinclude tests, documentation and further observations of data analysis techniquesused in this study in the form of descriptive analysis and qualitative analysis.Based on the results of observational data analysis that the activity of students in thefirst cycle is still low, and in cycle II, students are already active it is seen anincrease in student activity in cycle II of 67% and it will be related to studentlearning outcomes, A complete cycle I only 40% in cycle II of 63.33% means that theincrease in learning outcomes in cycle II compared to the cycle I that the learningoutcomes of entrepreneurship cycle II turned out better results, so it can beconcluded that entrepreneurial learning by applying the model of learning Think,write, and talk classroom can improve student learning outcomes.